A Simple HPLC Method for the Quantitative Determination of Silybin in Rat Plasma: Application to a Comparative Pharmacokinetic Study on Commercial Silymarin Products - Eun-Sol Ha; Dong-Gyun Han; Seong-Wook Seo; Ji-Min Kim; Seon-Kwang Lee; Woo-Yong Sim; In-Soo Yoon; Min-Soo Kim (Molecules, 2019)
Silybin (SBN) is a major active constituent of silymarin, a mixture of flavonoids found in fruits and seeds of milk thistle. The aim of this study was to describe a simple bioanalytical method for quantifying SBN in rat plasma. A simple protein deproteinization procedure with acetonitrile (ACN) was employed for plasma sample preparation. A reversed column and gradient elution of a mobile phase (mixture of phosphate buffer (pH 5.0) and ACN) were used for chromatographic separation. The selectivity, linearity (50−5000 ng/mL), precision, accuracy, recovery, matrix effect, and stability for this method were validated as per the current Food and Drug Administration (FDA) guidelines. Our method for SBN was applied to a comparative pharmacokinetic study on four different commercial silymarin products. This in vivo rat study demonstrated that product #4 significantly enhanced the relative oral bioavailability of SBN, as compared to product #1−3. Therefore, the bioanalytical method proposed herein could serve as a promising alternative for preclinical pharmacokinetic studies on silymarin products and, by extension, clinical use after partial modification and validation.